NILAI PELANGGAN, ATMOSFER DAN KEPUASAN PELANGGAN KARAOKE KELUARGA D’CLASS DI KOTA PALU - Lamasitudju, Moh. Salam M. S. (Katalogis, 2017)
The study intends to find out: 1) if custemers’ value and atmosphere have positive and significant influence on customers’ statisfaction in D’Class Family Karaoke; 2) if customers’ value has positive and significant influence on customers’ statisfaction in D’Class Family Karaoke; 3) if atmosphere has positive and significant influence on customers’ statisfaction in D’Class Family Karaoke. Type of study is causal descriptive, which explains the influence between variables through hypothesis testing involved 99 respondents who where selected through purposive sampling technique. Based on test with multiple linier regressions, the study conclused that: 1) customers’ value and and atmosphere simultaneously have positive and significant influence on customers’ statisfaction in D’Class Family Karaoke in Palu City;  2) customers’ value has positive and significant influence on customers’ statisfaction in D’Class Family Karaoke in Palu City; 3) atmosphere has positive and significant influence on customers’ statisfaction in D’Class Family Karaoke in Palu City.